ANALISIS WACANA KRITIS IKLAN ROKOK DJARUM 76 - Atikah Nurul Asdah; Jufri Jufri; Syamsudduha Syamsudduha (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
Critical Discourse Analysis of Djarum Cigarettes 76. This study aims to determine the form of choice of words and the meaning of the references contained in the choice of Indonesian language discourse in the Djarum 76 cigarette ad edition "Om Jin: I Give One Request". The approach used in this study is descriptive qualitative. The results of the study indicate that the Djarum 76 advertisement shows a phenomenon that meaning is dead because the Djarum 76 advertisement offers a very open interpretation to anyone who will enjoy it. The conclusion behind the critical discourse echoed, veiled ideology and interests related to capitalism.